The Approaches on Medieval Iberian History in Didactic Books - Oliveira, Fabiana de; Avelino, Maria Aparecida (História: Questões e Debates, 2018)
The present reflection is the result of a qualitative documentary research that aimed to study the approaches of medieval Iberian History in textbooks of History and from this perspective to reflect on cultural, ethnic and religious diversity. Thus, it is intended to reconcile two concerns: bring to light the discussion of the theme of diversity in a specific period and space, and investigate how this theme is being approached in didactic publications. Considering the cultural, ethnic and religious diversity of the Medieval Iberian Peninsula, what are the approaches in the History textbooks, of the 1st year of High School, approved in the National Program of Didactic Book for the High School 2015-2017? Thus is relevant to know how these themes are discussed in Iberian History problematizing the textbook as support for teaching proposals focused on this area of knowledge. The results lead us to affirm that the analyzed books show an expressive openness in what refers to contemporary historiographical discussions when they have a significant space to the medieval period, seeking to deconstruct myths and stereotypes. However, as regards to the contents of the Iberian Peninsula, a simplified and correlated approach with the historical process of other Europe regions such as France, England and Germany was noted. Specifically, on the cultural and religious diversity, fruit of the relations between Christians, Muslims and Jews in the Iberian Medieval, the mention occurred in a punctual way in the context of the Islamic expansion.